ANALISIS KESULITAN BELAJAR PESERTA DIDIK DALAM MENYELESAIKAN SOAL CERITA OPERASI PEMBAGIAN KELAS IV SEKOLAH DASAR - Imaduddin, Imaduddin; Mudzanatun, Mudzanatun; Mandar Sary, Ryky (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2025)
Learning difficulties are a common problem in elementary school teaching and learning activities, especially in mathematics. The results of a preliminary study that has been conducted indicate that there are learning difficulties that occur in the division material when solving story problems by grade IV students at an elementary school in Tersono District. The objectives of this study were (1) to analyze the difficulties experienced by students in solving story problems on division material for grade IV elementary schools and (2) to identify factors that influence learning difficulties experienced by students in solving story problems on division for grade IV elementary schools. The research approach used was qualitative with a phenomenological method. The data source was 9 grade IV students at an elementary school in Tersono District. Data collection techniques were carried out through tests and interviews. Data analysis techniques were done through data reduction, presentation, and conclusion. The validity of the data was determined through the triangulation of techniques and sources. The results of the study showed: (1) The difficulties experienced by students in solving story problems in the steps of understanding and exploring the problem (understand) were 24.4%, finding a strategy (strategy) was 26.7%, using a strategy to solve the problem (solve) was 37.8%, and looking back and reflecting on the solution obtained (look back) was 37.8%. (2) Internal and external factors influence factors that influence learning difficulties. Internal factors influencing learning difficulties amounted to 51.8%, namely physical and psychological factors. In comparison, external factors that influence learning difficulties amounted to 37.03%, namely family environment, community environment, and school environment factors.